Cold intolerance after brachial plexus nerve injury - Novak, Christine B. (Springer-Verlag, 2011)
BACKGROUND: The purpose of this study was to evaluate cold intolerance symptoms in patients with brachial plexus nerve injury. We hypothesized that higher levels of cold intolerance would be associated with more pain, greater disability, and unemployment. METHODS: Following research ethics board approval and patient consent, we included English-speaking adults more than 6 months following brachial plexus nerve injury. Patient questionnaires included Cold Intolerance Severity Scale (CISS), McGill Pain Questionnaire, SF-36, DASH, pain catastrophizing scale, and Post-traumatic Stress Disorder Checklist. Statistical analyses evaluated the relationships among the questionnaires and the independent variables. Multivariable linear regression evaluated the factors associated with the CISS. RESULTS: There were 61 patients, 20 women and 41 men (mean age 40 ± 17 years). The mean questionnaire scores indicated high scores in the CISS, DASH, and pain intensity. The CISS was significantly higher in women. The final regression model with CISS as the dependent variable included the following independent variables: McGill pain rating index, DASH score, and time since injury. Neither pain catastrophizing nor post-traumatic stress scores were retained in the final model. CONCLUSIONS: Patients with brachial plexus nerve injury reported substantial cold intolerance which was associated with the McGill pain rating index, upper extremity disability, and time since injury.